ナンキョク ショウワ キチ フキン ノ ジシン - 神沼, 克伊; カミヌマ, カツタダ; 赤松, 純平; アカマツ, ジュンペイ; Kaminuma, Katsutada; Akamatsu, Junpei (1987)
P(論文) 1957年に国際地球観測年が始まり, 地震観測点が設置されるまでは, 南極に震源のある地震は観測されていない。南極での地震観測が継続されるにしたがい, 南極大陸やその周辺海域での地震発生が報告されるようになった。過去20年間に4個の地震の震源が南極大陸内や沿岸に確認されている。その一つは東南極盾状地に位置している。マグニチュードはいずれも4ぐらいで, 南極大陸内にマグニチュード5以上の地震が起こっていないのも事実である。各観測点近傍の地震活動も, 国際地球観測年の頃は報告されている。昭和基地でも局地的な地震活動が認められているが, 1987年に始めたテレメータ観測でも, 局地的な地震が4カ月間に10個ほど記録された。これらの地震のマグニチュードは3以下で, 昭和基地でのP-S≒20秒, 北東方向160km付近に震源域があることがわかった。この震源域の付近は地質断層の存在も推定されており, このテクトニックな局地的地震と地質構造との関係も興味深い。 There were no earthquakes located in the Antarctic continent before the International Geophysical Year (IGY) in 1957. About ten seismic stations have been operated in the Antarctic continent since IGY. Four earthquakes were reported to loacte in and around the Antarctic continent since 1968. One of the four earthquakes which occurred in 1980 was located in Queen Maud Land, the east Antarctic shield area. The occurrence of small and microearthquakes around each seismic station has been reported. However, no earthquake locations were determined because the earthquakes were recorded at only one or two seismic stations. A tripartite seismic network of radiotelemetry was established at Syowa Station (69°S, 39°E) in 1987. Some tectonic earthquakes were recorded by the network. Magnitude of the erathquakes is less than 3,and P-S≒20s. The earthquakes are estimated to be located at about 160km northeast of Syowa Station. The activity of the earthquakes in relation with the geological structure is a very important item in the Antarctic geoscience. departmental bulletin paper